Institutional Implementation of Civil Control in the Security System: Theoretical and Methodological Assessment - Kocharyan, Tigran; Shahumyan, Anahit (NAS RA)
In the process of establishing democracy by the state, the institution of civil control by the society (non-governmental circles) is one of the modern primary elements. It is carried out by subjects of civil control, in particular, nongovernmental organizations, individuals, public organizations, and several other competent authorities. Civil control over the security sector is a more complex and ambiguous process, which, on one hand, ensures the transparency and efficient operation of the sector, but on the other hand, makes it more vulnerable. Among state institutions, the role of parliament in exercising control over the security system is crucial, especially in states with a parliamentary government model, where the government is accountable to the parliament.
Keywords: Political Studies; Political Philosophy